2015
DOI: 10.1080/1041794x.2014.981284
|View full text |Cite
|
Sign up to set email alerts
|

Applying Instructor Communication Behaviors and Learning Outcomes to the Pediatrician-Parent Context

Abstract: To examine instructional communication behaviors in the medical context and to explore the role of health literacy in pediatrician-parent relationships, the current study assessed parents' (N ¼ 299) perceptions of their pediatricians' nonverbal immediacy, clarity, and verbal receptivity and their own communication satisfaction, affective learning, and cognitive learning. Results demonstrated that when pediatricians are nonverbally immediate, clear, and verbally receptive, parents report that they are satisfied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 45 publications
(53 reference statements)
2
7
0
Order By: Relevance
“…It also supports the view that trainees do not overlook the performance of the trainer in determining the effectiveness of a training program (Diamantidis and Chatzoglou, 2012). This finding complements the results of prior studies on communication behaviors of the instructors that enhance communication satisfaction such as verbal clarity, humor, confirmation, (LaBelle et al , 2015; Sidelinger, 2014; Myers and Goodboy, 2014) and that reduce communication satisfaction such as compulsive communication, inappropriate conversations and misbehaviors were found to reduce communication satisfaction (Sidelinger and Bolen, 2016; Sidelinger et al , 2015; Sidelinger, 2014; Goodboy and Myers, 2015).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…It also supports the view that trainees do not overlook the performance of the trainer in determining the effectiveness of a training program (Diamantidis and Chatzoglou, 2012). This finding complements the results of prior studies on communication behaviors of the instructors that enhance communication satisfaction such as verbal clarity, humor, confirmation, (LaBelle et al , 2015; Sidelinger, 2014; Myers and Goodboy, 2014) and that reduce communication satisfaction such as compulsive communication, inappropriate conversations and misbehaviors were found to reduce communication satisfaction (Sidelinger and Bolen, 2016; Sidelinger et al , 2015; Sidelinger, 2014; Goodboy and Myers, 2015).…”
Section: Discussionsupporting
confidence: 86%
“…To explicate further, first, trainer task communication shall be positively related with trainee communication satisfaction. This expectation is in line with the findings of several studies that found a positive relation between several instructor communicative behaviors and communication satisfaction (LaBelle et al, 2015;Sidelinger, 2014;Myers and Goodboy, 2014). Then trainer task communication shall have negative relations with both behavioral uncertainty (self) and behavioral uncertainty (others).…”
Section: Mediation Of Behavioral Uncertainty (Both Self and Trainer)supporting
confidence: 91%
See 1 more Smart Citation
“…Most recently, convergence theory was used to understand recruiting messages within the direct sales industry (Martin & Rawlins, 2018) and team decision making (Horila, 2021). Combining instructional communication theory and organizational communication theory (Kearney, 2008; LaBelle et al, 2015) could assist managers and trainers from a pragmatic view and expand communication scholarship in two ways. One, communication is interdependent, and two, perception understanding and its importance to organizational communication regarding training speaks to how critical effective communication is for establishing an effective learning environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…• Arianism held that Jesus, while not merely mortal, was not eternally divine and was, therefore, of lesser status than the Father. (44) Christianity The church also entered into a long period of missionary activity and expansion among the various tribes. Catholicism Catholicism spread among the Germanic peoples, the Celtic and Slavic peoples, the Hungarians, and the Baltic peoples.…”
Section: Edict Of Milan Edict Of Milanmentioning
confidence: 99%